2011
DOI: 10.4103/0974-8490.79115
|View full text |Cite
|
Sign up to set email alerts
|

Partial in vitro and in vivo red scorpion venom neutralization activity of Andrographis paniculata

Abstract: Objective:Red scorpion (Mesobuthus tamulus) is the most lethal among all poisonous species of scorpions. Envenoming by Mesobuthus tamulus is quite common along the western coast of India, without any established therapy. Andrographis paniculata is one of the plants that has long been used in traditional herbal medicine for the treatment of poisoning by animal bites. Hence, the study was planned to evaluate the ethanolic extract of Andrographis paniculata for the treatment of Mesobuthus tamulus envenoming.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…[ 21 22 ] It was also shown that A. paniculata extract neutralized the inflammatory and lethal effects induced by Indian Red Scorpion. [ 23 ] Our study further confirms the anti-inflammatory potential of A. paniculata by inhibiting Group IIA sPLA 2 .…”
Section: Resultssupporting
confidence: 79%
“…[ 21 22 ] It was also shown that A. paniculata extract neutralized the inflammatory and lethal effects induced by Indian Red Scorpion. [ 23 ] Our study further confirms the anti-inflammatory potential of A. paniculata by inhibiting Group IIA sPLA 2 .…”
Section: Resultssupporting
confidence: 79%
“…LD 99 of M. tamulus scorpion venom used was calculated by probit analysis and the dose was 25.12 μg/g. [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…[20] LD 99 of M. tamulus venom is found to be 25.12 μg/g. [16] Ethanolic extract of AP in the dose of 1 g/kg was found to have some protective effect against red scorpion venom in mice. [16] Since 1997 ASV is available for clinical use in India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations